Pain after whiplash: a prospective controlled inception cohort study. Issue 3 (1st March 1999) - Obelieniene, Diana; Schrader, Harald; Bovim, Gunnar; Misevičiene, Irena; Sand, Trond
Abstract : OBJECTIVES: In Lithuania, there is little awareness of the notion that chronic symptoms may result from rear end collisions via the so-called whiplash injury. After most such collisions no contact with the health service is established. An opportunity therefore exists to study post-traumatic pain without the confounding factors present in western societies. METHODS: In a prospective, controlled inception cohort study, 210 victims of a rear end collision were consecutively identified from the daily records of the Kaunas traffic police. Neck pain and headache were evaluated by mailed questionnaires shortly after the accident, after 2 months, and after 1 year. As controls, 210 sex and age matched subjects were randomly taken from the population register of the same geographical area and evaluated for the same symptoms immediately after their identification and after 1 year. RESULTS: Initial pain was reported by 47% of accident victims; 10% had neck pain alone, 18% had neck pain together with headache, and 19% had headache alone. The median duration of the initial neck pain was 3 days and maximal duration 17 days. The median duration of headache was 4.5 hours and the maximum duration was 20 days. After 1 year, there were no significant differences between the accident victims and the control group concerning frequency and intensity of these symptoms. CONCLUSIONS: In a country were there is no preconceived notion of chronic pain arising from rear end collisions, and thus no fear of long term disability, and usually no involvement of the therapeutic community, insurance companies, or litigation, symptoms after an acute whiplash injury are self limiting, brief, and do not seem to evolve to the so-called late whiplash syndrome.